Ceramic Hollow Fibre Constructs for Continuous Perfusion and Cell Harvest from 3D Hematopoietic Organoids - Mark C. Allenby; Asma Tahlawi; José C. F. Morais; Kang Li; Nicki Panoskaltsis; Athanasios Mantalaris (Hindawi Limited, 2018)
Tissue vasculature efficiently distributes nutrients, removes metabolites, and possesses selective cellular permeability for tissue growth and function. Engineered tissue models have been limited by small volumes, low cell densities, and invasive cell extraction due to ineffective nutrient diffusion and cell-biomaterial attachment. Herein, we describe the fabrication and testing of ceramic hollow fibre membranes (HFs) able to separate red blood cells (RBCs) and mononuclear cells (MNCs) and be incorporated into 3D tissue models to improve nutrient and metabolite exchange. These HFs filtered RBCs from human umbilical cord blood (CB) suspensions of 20% RBCs to produce 90% RBC filtrate suspensions. When incorporated within 5 mL of 3D collagen-coated polyurethane porous scaffold, medium-perfused HFs maintained nontoxic glucose, lactate, pH levels, and higher cell densities over 21 days of culture in comparison to nonperfused 0.125 mL scaffolds. This hollow fibre bioreactor (HFBR) required a smaller per-cell medium requirement and operated at cell densities > 10-fold higher than current 2D methods whilst allowing for continuous cell harvest through HFs. Herein, we propose HFs to improve 3D cell culture nutrient and metabolite diffusion, increase culture volume and cell density, and continuously harvest products for translational cell therapy biomanufacturing protocols.